"Flexures and bends of the large intestine: Current terminology and a suggestion to simplify it". Issue 4 (30th November 2022) - Wozniak, Slawomir; Quondamatteo, Fabio; Paulsen, Friedrich
Abstract: There are a number of inconsistencies in the description of the bends of the colon down to the anus. This is historically based on the fact that anatomists saw the colon in its position in the abdominal cavity down to the pelvis and thus from the "outside" and also described it in this way. This view is still useful in clinical practice today (e.g. for the abdominal surgeons). For the greater part of clinicians, however, the view has shifted due to modern endoscopy. This allows examiners to see the terminal section of the intestine and the colon from the "inside". To accommodate both "ways of looking" in terms of modern medicine, we have been guided by today's clinical needs, and here we attempt to reconcile these with the historically evolved anatomical terms to create a nomenclature that meets all the needs of students, anatomists and clinicians looking at the large intestine from the inside and outside. With this in mind, we propose to speak of colic flexures (right colic flexure = RCF = hepatic flexure, flexura coli sinistra ; left colic flexure = LCF = splenic flexure, flexura coli dextra ; descending‐sigmoid flexure = DSF; sigmoid‐rectum flexure = SRF) for the colon ( colon ). For the rectum ( rectum ), we suggest the term bend (superior, intermediate and inferior) when viewed in the frontal plane, the term curvature (sacral curvature; anorectal curvature = perineal curvature) when viewed in the sagittal plane. Abstract : The large intestine flexures, bends and curvatures. Are we ready for changes….? Bends and curvatures introduced to colon terminology.